Uterine Microbiota: Residents, Tourists, or Invaders? - Baker, James M.; Chase, Dana M.; Herbst-Kralovetz, Melissa M. (Frontiers in Immunology, 2018)
Uterine microbiota have been reported under various conditions and populations, however it is uncertain the level to which these bacteria are residents that maintain homeostasis, tourists that are readily eliminated or invaders that contribute to human disease. This review provides a historical timeline and summarizes the current status of this topic with the aim of promoting research priorities and discussion on this controversial topic. Discrepancies exist in current reports of uterine microbiota and are critically reviewed and examined. Established and putative routes of bacterial seeding of the human uterus and interactions with distal mucosal sites are discussed. Based upon the current literature we highlight the need for additional robust clinical and translational studies in this area. In addition, we discuss the necessity for investigating host-microbiota interactions and the physiologic and functional impact of these microbiota on the local endometrial microenvironment as these mechanisms may influence poor reproductive, obstetric and gynecologic health outcomes and sequelae.